The COVID-19 pandemic: how can risk science help?. Issue 7 (2nd August 2020) - Aven, Terje; Bouder, Frederic
Abstract: This paper reflects on how risk science, with its concepts, principles, approaches, methods and models, can support the actual assessments, communication and handling of the vulnerabilities and risks related to the Coronavirus (Covid-19) pandemic. We highlight the importance of acknowledging uncertainty as a main component of risk, in order to properly characterize and communicate risk, as well as to understand the difference between professional risk judgements and risk perception. We challenge the use of the commonly referred to phrase that the policies adopted are science-based, in a situation like this characterized by fundamental uncertainties about the underlying phenomena and the effects of possible interventions. Arguments are provided for a 'balanced' use of precaution, combined with adaptive management and learning.